Hard to handle - Foster, Lori 1958- (New York Berkley Pub., 2008)
When his uncle secretly hires a life coach to get him back into the ring, Supreme Battle Challenge fighter Harley Handleman, recovering from the death of his mother and his failure to win the title belt, is knocked out by Anastasia Bradley, who teaches him how to live again.
Tac-2460g donated by UPVTC Gender Development Program on 07 Jan 2015.
Keywords: Mixed martial arts -- Fiction; Man-woman relationships -- Fiction; Love stories